Progress Report: Challenges and opportunities for creating a climate-smart food system in the Philippines and Vietnam - Baruah, Sampriti; Mohanty, Samarendu (2019)
This report documents the activities carried out under the CIP-CCAFS study on identifying opportunities and challenges for creating a climate-smart food system in the Philippines and Vietnam. Specifically, four provinces (Tarlac, Nueva Ecija, Leyte, and Samar) were studied in the Philippines while four provinces (Thai Binh, Bac Ninh, Tra Vinh, and Bac Lieu) were also selected in Vietnam. The methodology followed a mixed methods research wherein quantitative and qualitative data collection and analysis were both used. The data generated from the two methodologies were analyzed and compared with each other to come up with an interpretation. The quantitative data analyzed was the supply transformation and consumer demand while the qualitative data was agricultural production and policies and market structures. The seasonal calendar was also used to understand livelihood and agricultural activities, seasons prevalent in the community, workload, and division of labor between men and women.